Spatio-temporal image correlation (STIC) used by general obstetricians is marginally clinically effective compared to 2D fetal echocardiography scanning by experts - Prapat Wanitpongpan (2018)
Objectives: To assess the effectiveness of spatio-temporal image correlation (STIC) used by general obstetricians as compared with 2D scanning. Methods: As many as 30 pregnant women at 17-21 weeks' gestation were enrolled. 2D ultrasound was performed by a fetal echocardiologist; STIC was performed by a general obstetrician. Time, accuracy of measurement of diameter of great vessels and quality of the pictures obtained by the two methods were compared. Results: The mean time required by 2D ultrasound was significantly shorter than that by STIC (5.2 ± 1.9 min vs 9.8 ± 2.7 min; P < 0.001). The measurement of the diameter of the great vessels showed some difference but the mean score of the pictures obtained by both methods were not significantly different. By using 2D ultrasound, acceptable quality pictures were obtained in 51.9, 44.4 and 51.9% of cases for 4-chamber, 5-chamber and 3-vessel views, respectively. Meanwhile by using STIC, the percentages were 77.8, 59.3 and 37%. Conclusion: Our study suggested that STIC used by general obstetricians to check normality of fetal cardiac structures at 17-21 weeks' gestation has marginal clinical effectiveness when compared to 2D scanning by a fetal echocardiologist, and should need some improvement before it can be used as a tool to expand a fetal cardiac screening program. Copyright © 2008 John Wiley & Sons, Ltd.